Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
You always start by simplifying.
6b-49=2(b-3) becomes 6b-49=2b-6
From there you can group the b's together by subtracting 2b from both sides, leaving you with 4b-49=-6
Now you can get the b's alone by adding 49 (to cancel out -49) to both sides, giving you 4b=43, You're still trying to get b by itself, so what you'll do is divide both sides by 4, giving you b=10.75
6b-49=2(b-3) becomes 6b-49=2b-6
From there you can group the b's together by subtracting 2b from both sides, leaving you with 4b-49=-6
Now you can get the b's alone by adding 49 (to cancel out -49) to both sides, giving you 4b=43, You're still trying to get b by itself, so what you'll do is divide both sides by 4, giving you b=10.75
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.